Evaluation of the interaction between microencapsulated Bifidobacterium BB-12 added in goat's milk Frozen Yogurt and Escherichia coli in the large intestine. (January 2020) - Verruck, Silvani; Barretta, Clarissa; Miotto, Marília; Canella, Maria Helena Machado; de Liz, Gabriela Rodrigues; Maran, Bruna Marchesan; Garcia, Sofia Grechi; da Silveira, Sheila Mello; Vieira, Cleide Rosana Werneck; da Cruz, Adriano Gomes; Prudencio, Elane Schwinden
Graphical abstract: Highlights: Bifidobacterium BB-12 and Escherichia coli interaction in the gut were reported. Frozen Yogurt was able to deliver encapsulated probiotic bacteria to the colon. Bifidobacteria inhibit pathogenic bacteria in the large intestine. Use of inulin as encapsulant agent for bifidobacteria improves antagonist effect. The phenomenon of viable but not-culturable cells of E. coli was observed by qPCR. Abstract: Goat milk and goat milk and inulin were used as encapsulating agents of Bifidobacterium BB-12 and applied in Frozen Yogurt (GF2 and GF3, respectively) in order to evaluate the antagonistic effect against Escherichia coli . GF1 is a control containing only Escherichia coli . Simulation of gastrointestinal digestion occurred sequentially. Quantification of Bifidobacterium BB-12 was performed using plate counting while E. coli count was compared with quantification by qPCR with viable and nonviable cell differentiation. The Bifidobacterium BB-12 count was <1.0, 9.23 and 9.11 log CFU g −1 for GF1, GF2 and GF3, respectively. In the ascending colon, all samples showed E. coli counts of approximately 5 log CFU g −1 by plate counting and by qPCR. Throughout the transverse (24 h) and descending colon (48 h) samples GF2 and GF3 showed decrease in E. coli number. GF3 showed higher decrease of E. coli in the descending colon because of inulin bifidogenic characteristic. The production of organic acids by bifidobacteria was directly related to the decrease in the E. coli count. In plate counts, E. coli was not detected for the GF3 sample in the descending colon. However, when quantified by qPCR the sample presented amplification that corresponded to 3 log CFU g −1 . In this way, it was possible to observe the phenomenon of the viable but not-culturable cells of E. coli . Finally, it is recommended the microcapsule produced with goat milk and the inulin for application in goat milk products, due to the better antagonist effect against E. coli .